2022
DOI: 10.3390/coatings12020209
|View full text |Cite
|
Sign up to set email alerts
|

Research into Carbon Dioxide Curing’s Effects on the Properties of Reactive Powder Concrete with Assembly Unit of Sulphoaluminate Cement and Ordinary Portland Cement

Abstract: Excessive emissions of carbon dioxide can lead to greenhouse effect thus destroying the ecological balance. Therefore, effective measures need to be taken to reduce the emission of carbon dioxide. In this study, the influence of carbon dioxide curing on the mechanical strength and NaCl freeze-thaw deterioration of reactive powder concrete (RPC) with the assembly unit of sulphoaluminate cement and ordinary Portland cement was investigated. The ratio of sulphoaluminate cement ranged from 0% to 100% by the total … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…The first one breaks down over time, and the second one breaks down with ambient temperatures. New phases formed instead of Са(ОН) 2 play a significant role in the formation of the structure of the cement stone, as their breakdown in some cases reduces the strength [4].…”
Section: Research Conditions and Methodsmentioning
confidence: 99%
“…The first one breaks down over time, and the second one breaks down with ambient temperatures. New phases formed instead of Са(ОН) 2 play a significant role in the formation of the structure of the cement stone, as their breakdown in some cases reduces the strength [4].…”
Section: Research Conditions and Methodsmentioning
confidence: 99%
“…Results showed that 10% limestone substitution improves concrete's properties (Tu et al, 2018). However, there are a few research studies on the CO2 curing of RPCs (Cao et al, 2022), where they considered the combination of 10% CO2 and 90% air as the carbonation curing media. Therefore, CO2 curing of RPCs is investigated in this study, where waste limestone powder was substituted as silica sand.…”
Section: Co2 Curing Of…mentioning
confidence: 99%
“…CO 2 curing on building materials provides ideas for its absorption [7]. Additionally, prior research pointed out that CO 2 curing can effectively improve the mechanical strengths and the durability of cement-based materials [8,9]. Moreover, as described in some journals [10], the drying shrinkage rate of cement-based materials is decreased by CO 2 curing.…”
Section: Introductionmentioning
confidence: 99%